2018
DOI: 10.1002/eco.2061
|View full text |Cite
|
Sign up to set email alerts
|

Biocrust research: A critical view on eight common hydrological‐related paradigms and dubious theses

Abstract: Although being relatively young, research on biocrusts has already yielded numerous paradigms and/or dubious theses. The very existence of these “truths” may lead to erroneous conclusions and/or hinder research on these topics. In the current summary, eight paradigms and dubious theses are examined: (a) Biocrusts require physical crusts for establishment; (b) plant establishment is necessary for biocrust establishment on dunes; (c) developmental stages of biocrusts are often regarded as successional stages; (d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(45 citation statements)
references
References 235 publications
(501 reference statements)
1
40
1
Order By: Relevance
“…Similarly, Baruch and Goring-Morris [82] reported that the Negev was covered by more mesic and denser woody vegetation during the Terminal Pleistocene, due to higher humidity. Denser vegetation would more efficiently trap sand particles [83]. This probably includes some sand from weathering of the underlying sandstones in the Petra region.…”
Section: Vegetation Biocrusts and Clast Pavementsmentioning
confidence: 99%
“…Similarly, Baruch and Goring-Morris [82] reported that the Negev was covered by more mesic and denser woody vegetation during the Terminal Pleistocene, due to higher humidity. Denser vegetation would more efficiently trap sand particles [83]. This probably includes some sand from weathering of the underlying sandstones in the Petra region.…”
Section: Vegetation Biocrusts and Clast Pavementsmentioning
confidence: 99%
“…The hilltop ruin soils from the Petra region (the triclinium JF site 124/1 and Umm Saysaban, no. [67][68][69][70][71] are chemically similar and cluster in the lower center of the diagram, with negative values of PC2 and values of PC1 around 0. In contrast, samples from the sandstone terrace (samples Jh site 33, no.…”
Section: Statistical Comparison Of Element Concentrationsmentioning
confidence: 99%
“…This seems due to a contribution from nearby sandstone cliffs: proximity to such local sources leads to higher supply of sediment, in this case, rich in medium sand. In addition, the agricultural use of the monastery garden, probably with cistern-based irrigation, could have led to stronger presence of vegetation, which has been found to favor the trapping of sand [70].…”
Section: Effects Of Proximity To Local Sediment Sources and Dust Fixamentioning
confidence: 99%
“…On the Colorado Plateau, well-developed lichen, moss, and dark-pigmented biocrusts tend to have greater levels of aggregate stability and surface roughness than biocrusts dominated by lightpigmented cyanobacteria (Fischer et al, 2010;Warren, 2001), which are often considered early successional (Belnap et al, 2013, but see Kidron, 2018). The most notable differences between plots with stabilizer and others were the significantly higher levels of both EPS and aggregate stability ( Figure 2), variables that were highly correlated (R 2 = 0.58, p = .002).…”
Section: Biocrust Restoration and Erosion Processesmentioning
confidence: 99%
“…On the Colorado Plateau, well-developed lichen, moss, and dark-pigmented biocrusts tend to have greater levels of aggregate stability and surface roughness than biocrusts dominated by lightpigmented cyanobacteria (Fischer et al, 2010;Warren, 2001), which are often considered early successional (Belnap et al, 2013, but see Kidron, 2018). The enhanced roughness and stability of welldeveloped biocrusts likely counteract the effects of hydrophobicity and pore clogging on infiltration by biocrust biomass (as both filamentous cyanobacteria and other organisms are abundant in these biocrusts), but this may depend on rainfall intensity (Rodríguez-Caballero et al, 2013).…”
Section: Biocrust Restoration and Erosion Processesmentioning
confidence: 99%